“His tongue seems shorter”: experiences of caregivers of managing communication with people with Parkinson disease in Malaysia - Altaher, Abeer Muneer; Chu, Shin Ying; Tan, Joo Siang; Sathiyasenan, Sai Tarishini; Hersh, Deborah; Mustaffa Kamal, Rahayu (Wolters Kluwer Health, 2023)
This qualitative study explored Malaysian caregivers’ experiences when caring for people with Parkinson disease (PD). Semistructured interviews (n = 10) were conducted, transcribed verbatim, and analyzed using thematic analysis. Four major themes and 9 subthemes emerged from the challenges faced by these caregivers. The 4 themes were “communication challenges,” “coping with communication challenges,” “becoming more dependent,” and “reduction in social participation.” Caregivers often demonstrated poor knowledge of PD and reported communication, physical, and psychosocial impacts affecting both them and the person with PD. To ensure the well-being of both caregivers and dependents with PD, the communication and social participation needs of caregivers and dependents should be considered during assessment and the planning of intervention